2018
DOI: 10.1249/mss.0000000000001702
|View full text |Cite
|
Sign up to set email alerts
|

Small-Sided Soccer in School Reduces Postprandial Lipemia in Adolescent Boys

Abstract: Compared with duration-matched inactivity (CON), after-school small-sided soccer (SOC) and treadmill exercise (TM) resulted in a similar, moderate reduction of postprandial lipemia in adolescent boys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…Whilst the cognitive benefits following Football were exclusive to high-fit individuals and the domain of working memory in the present study, there was also no evidence of a decline in performance for the low-fit participants because of exercise. This suggests that games-based exercise, such as Football, can still be a valid mode of activity for young people, given the known health benefits [54], the popularity [46] and the ease of access to the equipment needed.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the cognitive benefits following Football were exclusive to high-fit individuals and the domain of working memory in the present study, there was also no evidence of a decline in performance for the low-fit participants because of exercise. This suggests that games-based exercise, such as Football, can still be a valid mode of activity for young people, given the known health benefits [54], the popularity [46] and the ease of access to the equipment needed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown an intermittent football simulation protocol to be as effective as continuous running for lowering postprandial TG in a group of children [8] and young adults [9]. In addition, we found that a 9-a-side football match can lower postprandial TG measures in normal as well as overweight individuals [10], while Smallcombe et al [11] recently reported a small-sided football match resulted in a similar moderate reduction of postprandial TG in adolescent boys, compared to continuous treadmill running. However, these studies have solely examined the effects of an acute bout of football activity.…”
Section: Introductionmentioning
confidence: 46%
“…After each exercise session, the data were downloaded to Team AMS software (Team AMS, GPSports). The variables of interest were total distance covered (m) as well as the distance covered in six different speed categories: standing (≤0.4 km•h-−1 ), walking (>0.4 to 3.0 km•h −1 ), low-intensity running (>3.0 to 8.0 km•h −1 ), moderate-intensity running (>8.0 to 13.0 km•h −1 ), high-intensity running (>13.0 to 18.0 km•h −1 ) and sprinting (>18.0 km•h −1 ) (Smallcombe et al, 2018).…”
Section: Exercise Protocolmentioning
confidence: 99%
“…However, there is little research investigating the effects of team games on risk factors for cardiometabolic disease in adolescents. Smallcombe et al, (2018) employed a 48 min bout of football (using small-sided games) compared to duration-matched treadmill running in adolescent boys (12.7-13.3 y). The bout of football led to greater improvements in postprandial lipaemia in adolescent boys -despite less distance being covered in the small-sided games.…”
Section: Introductionmentioning
confidence: 99%